教師知識管理與教學效能關係之後設分析 A Meta-analysis of the Relationship between Teachers' Knowledge Management and Teaching Effectiveness - 陳柏霖 Po-Lin Chen (National Changhua University of Education, 2015)
本研究旨在探討教師知識管理與教學效能的實際效果，藉由統合2004 至2013 年的27 篇博碩士論文的研究數據，探討教師知識管理與教學效能兩變項的相關性、調節變項的影響、及跨變項間相關作用的結果。研究方法上採用後設分析，研究結果指出，教師知識管理與教學效能的平均效應量為.85，表示具有正相關且高度效應量。根據研究結果，提出實務建議與未來研究建議。 The purpose of this study is to explore the effects of teachers' knowledge management for teaching effectiveness. Researcher analyzed mean correlations, moderators' effect, and correlation across the two variables which are teachers' knowledge management and teaching effectiveness by collecting data consisted of 27 theses published in 2004-2014. Meta-analysis was used to examine the effects of teachers' knowledge management on teaching effectiveness. The main conclusions are as follows: There are significant positive correlation and high effect size (which reaches to 0.85) between teachers' knowledge management and teaching effectiveness. According to the results of the study, some practical suggestions are made for further studies.